PENGARUH PENGEMBANGAN KARIR DAN KOMITMEN ORGANISASI TERHADAP KEPUASAN KERJA KARYAWAN (STUDI KARYAWAN BAGIAN UMUM PT PERKEBUNAN NUSANTARA V PEKANBARU) - Junni Yenni Marbun; Kasmirudin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This research is to detecting the effect of Career Development And Organizational Commitment To Employees Statisfaction Common Parts In The PT Perkebunan Nusantara V Pekanbaru.This research used questionnaire with measurement scale that is Likert scale which analyzed by validity test, reliability test, simple regression analysis, multiple regression analysis, correlation analysis of determination, t test, and f test with the help of using SPSS software ver. 17 for windows. The number population from this research 94 persons with 48 employees which consists of employee leadership and executive employee on PT Perkebunan Nusantara V Pekanbaru as the sample, which calculated by Slovin formula.From the results of tests performed indicate that the career development an organizational commitment has positive and significant impact on employees statisfaction general affair in the PT Perkebunan Nusantara V Pekanbaru. Which is the determination coefficient values shown that the variable of career development and organizational commitment constribute to variable of employees statisfaction by 49.5% while the remaining 50.5% is influenced by other variables outside the model.Keywords : career development, organizational commitment, employees statisfaction